Draft Annual Plan 2000-2001 Government of Mizoram - Planning Commission (Planning Commission, 2000)
Resource base of Mizoram being extremely Poor, no significant improvement in the mobilisation of States own resources is expected during 2000-2001 in spite of several initiatives taken up in this regard. Besides, the available indications suggest that the Central assistance for Plan funding would remain more or less at current year's level. As such, the Draft Annual Plan 2000-2001 has been prepared for implementation at a cost of Rs. 360 Crores - the same as current year.
Government of Mizoram, Planning and Programme Implementation Department